A review of studies on gut microbiota and levodopa metabolism - Zhong, Zhe; Ye, Min; Yan, Fuling (Frontiers in Neurology, 2023)
Parkinson’s disease (PD) is the second most common neurodegenerative disease globally. Levodopa (L-dopa) has been the cornerstone for treating Parkinson’s since the 1960s. However, complications such as “wearing-off” and dyskinesia inevitably appear with disease progression. With the further development of microbiomics in recent years, It has been recognized that gut microbiota plays a crucial role in Parkinson’s disease pathogenesis. However, Little is known about the impact of gut microbiota in PD treatment, especially in levodopa metabolism. This review examines the possible mechanisms of gut microbiota, such as Helicobacter pylori, Enterobacter faecalis, and Clostridium sporogenes, affecting L-dopa absorption. Furthermore, we review the current status of gut microbiota intervention strategies, providing new insights into the treatment of PD.